2020
DOI: 10.3748/wjg.v26.i33.4996
|View full text |Cite
|
Sign up to set email alerts
|

Liver fat accumulation measured by high-speed T2-corrected multi-echo magnetic resonance spectroscopy can predict risk of cholelithiasis

Abstract: BACKGROUND Liver fat accumulation is associated with increased cholesterol synthesis and hypersecretion of biliary cholesterol, which may be related to the development of cholelithiasis. AIM To investigate whether liver fat accumulation measured by high-speed T2-corrected multi-echo magnetic resonance spectroscopy (MRS) is a risk factor for cholelithiasis. METHODS Forty patients with cholelithiasis and thirty-one healthy controls were retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Further, the ability of MR to separate the water resonance from other confounding proton resonance sources (e.g., lipids) enables the direct analyses of the transverse relaxation rate of tissue water (R2 water ) [16,17]. The high-speed T2-corrected multi-echo (HISTO) H 1 MR spectroscopy technique, where a single voxel sequence allows for quantification of tissue R2 water , has been developed [18,19]. Relaxometry has been widely employed in measuring myocardial and hepatic siderosis [20,21], and liver R2 water has been studied in relation to hepatic iron content [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the ability of MR to separate the water resonance from other confounding proton resonance sources (e.g., lipids) enables the direct analyses of the transverse relaxation rate of tissue water (R2 water ) [16,17]. The high-speed T2-corrected multi-echo (HISTO) H 1 MR spectroscopy technique, where a single voxel sequence allows for quantification of tissue R2 water , has been developed [18,19]. Relaxometry has been widely employed in measuring myocardial and hepatic siderosis [20,21], and liver R2 water has been studied in relation to hepatic iron content [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other imaging modalities, MRI-PDFF has the highest diagnostic accuracy for the quanti cation of LFC and is commonly used in NASH trials. [10] Few studies have discussed the clinical characteristics of adult MAFLD based on MRI-PDFF, [11][12][13] and limited biomarkers have been investigated. [14][15][16][17] Serum biomarkers such as cytokeratin 18 (CK18), broblast growth factor 19 (FGF19), and tissue inhibitor matrix metalloproteinase 1 (TIMP1) showed a strong correlation with disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Traditionally, MRS has been performed with multiple acquisitions under free-breathing conditions to achieve a high signal-to-noise ratio, 15 which commonly leads to line broadening and erroneous data acquisition due to motion and long acquisition times. [16][17][18] Recently, high-speed T 2 -corrected multiecho (HISTO) MRS was developed to assess lipids by using multiple short-echo times to correct T 2 bias and using long repetition times to correct T 1 bias by enabling the simultaneous acquisition of multiple echoes, 19,20 which is faster and more accurate in acquiring and measuring lipid components than traditional MRS. [21][22][23] Previous studies have shown the benefit of HISTO-MRS for the precise quantitative assessment of fatty deposition in the liver. 23,24 However, only one study has examined the utilization and feasibility of HISTO-MRS as a rapid and noninvasive MRS technique for quantifying the fat infiltration of skeleton muscles in children with confirmed DMD, 25 Meanwhile, the relationship between muscle fat infiltration measured by HISTO-MRS and clinical motor functional ability remains unknown.…”
mentioning
confidence: 99%
“…Traditionally, MRS has been performed with multiple acquisitions under free‐breathing conditions to achieve a high signal‐to‐noise ratio, 15 which commonly leads to line broadening and erroneous data acquisition due to motion and long acquisition times 16–18 . Recently, high‐speed T 2 ‐corrected multiecho (HISTO) MRS was developed to assess lipids by using multiple short‐echo times to correct T 2 bias and using long repetition times to correct T 1 bias by enabling the simultaneous acquisition of multiple echoes, 19,20 which is faster and more accurate in acquiring and measuring lipid components than traditional MRS 21–23 . Previous studies have shown the benefit of HISTO‐MRS for the precise quantitative assessment of fatty deposition in the liver 23,24 .…”
mentioning
confidence: 99%